ANALYSIS OF THE EFFECT OF INTEREST-BASED DEBT AND NON-HALAL INCOME ON THE VALUE OF SHARIA-COMPLIANT STOCK ISSUERS - Adlan, Muhammad; Mawardi, Imron (Universitas Airlangga, 2018)
This study aims to determine whether interest-based debt limitation and non-halal income limitation have significant effect on the firm value. Sharia stock issuers in Indonesia are obliged to pass several conditions set by the market regulator, some of them are limitations of the interest-based debt and non-halal income. This study assumes that the lower portion of interest-based debt and non-halal income, the more the investors will prefer the stocks, thus increasing the firm value. The subjects of this study are the companies listed on JII period 2013-2017. This study measures interest-based debt with ratio of interest-based debt devided by total debt, measures non-halal income with ratio of non-halal income divided by operating revenue, and measures the value of the firm with PBV. The analysis of this study using panel data regressions with fixed effects models with robust standard errors. The results shows that interest-based debt and non-halal income have no effects on the value of the firm, partially and simultaneously Keywords: Interest baseddebt, Non-halal income, Sharia stocks, Value of the firm